Inventário do Arquivo Oliveira Telles: uma contribuição para a preservação e o acesso a um patrimônio cultural sergipano - Oliveira, Cibele de Carvalho de (2021)
This work has as main objective the elaboration and availability of a summary inventory of the Oliveira Telles Fund, maintained by the Historical and Geographical Institute of Sergipe, in order to contribute to the promotion of better access and preservation of the documentation as cultural heritage. It is justified due to the need to build research instruments that have more specific information that can promote and facilitate access to information by researchers. It is also important to spread among society the existence of this great scholar hitherto unknown by a large part of the population. Through an exploratory-descriptive, documentary and qualitative research, the 29 documents belonging to the Oliveira Telles fund were raised and analyzed. This documentation includes articles, books, notebooks and notebooks, speeches, correspondence and fragments of poetic texts, where one can identify the most diverse subjects related to the history and culture of Sergipe. As for the theoretical framework, the following stand out: the context in which Information Science is inserted, information definitions, issues related to information in archival institutions, memory, research instruments and their respective ramifications, and the importance of preserving documentary collections for the maintenance of the collective memory of a people, according to scholars in each area. As a product, a summary inventory of the 29 documents belonging to the fund was prepared, based on the descriptive standardization rules present in the Brazilian Standard for Archival Description - NOBRADE, using as support the inventory models produced by Foundation Casa Rui Barbosa and the Inventory of Machado de Assis Archive, produced by the Brazilian Academy of Letters.